Disponibilidad a pagar por adquirir el servicio de agua y alcantarillado de las familias en las comunidades de Lobo Yacu y Nuevo Santo Tomás – Región Loreto 2022 - Zuñiga Guibin, Carlos Enrique (2024)
In Peru, the need to have drinking or safe water to avoid the appearance of water-related diseases allowed this research to be carried out to find out the willingness to pay for having water and sewage service in rural communities such as Nuevo Santo Tomas. (Amazon River) and Lobo Yacu (Nanay River), Punchana District, 2020. Descriptive statistics were used and the disease cost method was applied, estimating costs of treatment of the disease and the loss of time due to the affectation. It is concluded that both populations consider a calculated price of S/ 10.00 soles on average. and they would contribute 34% to sustain the service. Having treatment costs and lost time of S/ 29.52 soles. According to this average, residents would contribute 34% to maintain the service over time. Three diseases stand out due to lack of safe water intake; diarrhea and parasites (50 cases) and hepatitis (11 cases) prevail. Treatment costs: diarrhea of S/ 3246.20 soles, parasitic S/ 1800.00 soles and hepatitis S/ 4783.20 soles. The characteristics of these towns are that they extract water from the river (50%): it is boiled before consumption (84%). The transfer of water to homes takes thirty minutes. They maintain simple latrines (56%). They incinerate solid waste (62%) and sewage into the environment. They have a certain level of education, primary (68%) and secondary (32%), ages 41 to 50 years (28%) and 51 to 60 years (34%), they practice agriculture and have monetary income of S/400.00 to 700 soles (40%) and up to S/ 400.00 soles (30%).